DIGITAL DETOX AS A STRATEGY FOR ENHANCING ACADEMIC PERFORMANCE AND PSYCHOLOGICAL WELL-BEING AMONG STUDENTS - Gafurjanova Mashhura, (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
In today’s digital age, students spend a large amount of their time using smartphones, social media, and different online platforms. Although digital technologies make it easier to access information and support the learning process, spending too much time on screens can negatively affect students’ academic performance and psychological well-being. Recently, the idea of a digital detox has become popular as a way to reduce the harmful effects of constant technology use. This article examines how limiting screen time influences students’ concentration, productivity, and emotional condition. The study is based on the review of academic literature and observations of students’ experiences with digital technology. The results indicate that reducing the use of digital devices, especially social media, may help students improve their focus, lower stress levels, and sleep better. Consequently, students can become more organized and productive in their studies. The article concludes that practicing digital detox in a balanced and conscious way can help students develop a healthier relationship with technology and improve both their academic results and overall well-being.